1998
DOI: 10.1128/jb.180.18.4987-4990.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Region in Bacillus subtilis ς H Required for Spo0A-Dependent Promoter Activity

Abstract: Spo0A activates transcription in Bacillus subtilis from promoters that are used by two types of RNA polymerase, RNA polymerase containing the primary sigma factor, ςA, and RNA polymerase containing a secondary sigma factor, known as ςH. The region of ςA near positions 356 to 359 is required for Spo0A-dependent promoter activation, possibly because Spo0A interacts with this region of ςA at these promoters. To determine if the amino acids in the corresponding region of ςH are also important in Spo0A-dependent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The most probable reason for this conservation is that Spo0A must interact with other proteins whose amino acid sequences are conserved. It is known to interact with RNA polymerases containing either Sigma A or Sigma H (Buckner and Moran, 1998). The αE region of Spo0A in which mutations affect Sigma A‐dependent transcription (Buckner and Moran, 1998; Hatt and Youngman, 1998) shows significant amino acid variability in the two species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most probable reason for this conservation is that Spo0A must interact with other proteins whose amino acid sequences are conserved. It is known to interact with RNA polymerases containing either Sigma A or Sigma H (Buckner and Moran, 1998). The αE region of Spo0A in which mutations affect Sigma A‐dependent transcription (Buckner and Moran, 1998; Hatt and Youngman, 1998) shows significant amino acid variability in the two species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As for σ A , mutations in region 4.2 of σ H specifically decrease Spo0A∼P‐dependent stimulation of transcription directed by E‐σ H . Thus, the Q201A and R205A substitutions in σ H reduce Spo0A‐dependent transcription by E‐σ H from the spoIIA promoter without affecting transcription by E‐σ H from the spoVG promoter, which is Spo0A‐independent (Buckner and Moran, 1998). It seems therefore that Spo0A‐dependent transcription requires homologous regions of σ A and σ H .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, His, Cys and Ser substitutions at position 596 of s 70 reduce MalT-dependent activation of PmalK-lamB (Hu & Gross, 1985), and Lonetto et al (1998) demonstrated that FNR requires R596 for activation of PdmsA, and also PnarG in the absence of the co-regulator, NarL. In addition, at the Bacillus subtilis s H -dependent promoter, spoIIA, the Spo0A transcription factor requires the equivalent residue of s H , R205, to activate transcription (Buckner & Moran, 1998). Thus R596 in s 70 plays an important role in transcription activation at a variety of activator-dependent promoters.…”
Section: Other Class II Activators Also Interact With R596 Of S S S 70mentioning
confidence: 99%